PERAN ALAM BAWAH SADAR DALAM MEMBENTUK PERILAKU: KAJIAN LITERATUR BERDASARKAN TEORI PSIKOANALISIS - Devia Aprilianti; Rahma Aulia, Imalatul Khairat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sigmund Freud came up with the theory of psychoanalysis which consists of the subconscious mind and the conscious mind. Sigmund Freud's thinking says that consciousness is only a small part of mental life. Most of it is just the subconscious or unconscious, According to Sigmund Freud's psychoanalytic theory, the subconscious mind is defined as a collection of feelings, thoughts, drives, and memories that are beyond consciousness. Freud believed that the unconscious continues to fulfill behavior even though people are not aware of it. The purpose of psychoanalytic theory counseling is to reshape the individual's character structure by making the unconscious conscious in the individual.